Minimization of Peeling Stress in Asymmetric Single-Lap Adhesive Joint Via Firefly Optimization Algorithm - Damilare Adewunmi; Chisom Samuel; Antonio Fontana (Advances in Engineering and Intelligence Systems)
This study presents a novel approach aimed at determining optimal parameters for minimizing peeling stress in asymmetric single-lap adhesive joints. Normal and shear stress distributions within this joint configuration are derived analytically through two-dimensional elasticity equations, demonstrating the accuracy of the analytical approach through comparison with finite element model. Peeling stress reduction is achieved through application of the Firefly optimization algorithm, where independent variables include the thicknesses of the adhesive and adherends layers. Under tensile loading conditions, the composite joint is analyzed assuming isotropic and linear elastic behavior of the adhesive and adherends layers. Findings indicate a significant reduction in peeling stress of approximately 31% with an optimal thickness ratio of 2.44 for adhesive. Moreover, an increase in the ratio of Young's modulus leads to decreased maximum tensile stress, particularly as the adhesive joint becomes more asymmetric. Additionally, augmenting the Young's modulus of the underlying adhesive induces a redistribution of stress on the contact surface of the softer adhesive layer, while maintaining relatively unchanged stress distribution on the opposing adhesive surface.